Isolasi dan karakterisasi bakteri yang berpotensi mengikat aflatoksin di rumen sapi - Dwi Sisriyenni; Suryahadi Suryahadi; Komang G Wiryawan; Dwierra Evvyernie; Dadik Pantaya (Politeknik Negeri Jember, 2021)
The purpose of this study was to examine the influence of aflatoxins on rumen fermentation in vitro and obtained rumen bacterial isolates capable of binding aflatoxin. This trial consisted of three stages. The first trial was a reduction of aflatoxin in the rumen in vitro. The second experiment was the isolation and characterization of rumen bacteria that could bind aflatoxin. The third stage was to test the holding capacity of aflatoxin by rumen bacteria. This study used cow rumens. The Research design used a randomized complete block design (RCBD) factorial 2x3 and 2 replications. The first factor was the presence of aflatoxin (with and without the addition of aflatoxin), the second factor was the type of feed (diet and glucose), and the third factor was the time of incubation (0 and 4 hours). The results showed the presence of aflatoxin did not affect rumen conditions (pH, volatile fatty acid (VFA), and rumen lactic acid concentration), and the results obtained 6 isolates and isolation of rumen bacteria to bind aflatoxin up to 50%.